Adsorption of CO, CO2 and H2 in Silicalite-1: measurements and simulations - Wirawan, Sang Kompiang; Petersson, Martin; Creaser, Derek (ASEAN Journal of Chemical Engineering, 2008)
Single component and mixture adsorption of CO2, CO and H2 in Silicalite-1 was studied with the step response experiments and through molecular simulations. Experiments were performed at 323.15, 373.15 and 473.15 K, and in the pressure range 10.13 to 81.06 kPa. CO2 adsorption was favored over CO during all studied conditions. The adsorption enthalpies were -24.3 and -13.5 kJ/mol for CO2 and CO respectively. Adsorption simulations were performed using the Grand Canonical Monte Carlo method. A new zeolite framework potential was derived, and was shown to give good agreement with the experimental results. The major reason for the higher saturation loading of CO2 compared to CO is however the stronger sorbate-zeolite attraction for CO2. The affinity for CO2 also causes a decrease in the adsorbed molar fraction of CO due to the competition with CO2.